2015
DOI: 10.1016/j.bbr.2014.11.030
|View full text |Cite
|
Sign up to set email alerts
|

Mouse genetic differences in voluntary wheel running, adult hippocampal neurogenesis and learning on the multi-strain-adapted plus water maze

Abstract: Moderate levels of aerobic exercise broadly enhance cognition throughout the lifespan. One hypothesized contributing mechanism is increased adult hippocampal neurogenesis. Recently, we measured the effects of voluntary wheel running on adult hippocampal neurogenesis in 12 different mouse strains, and found increased neurogenesis in all strains, ranging from 2 to 5 fold depending on the strain. The purpose of this study was to determine the extent to which increased neurogenesis from wheel running is associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 44 publications
2
22
0
1
Order By: Relevance
“…This difference was not due to gross learning or motoric effects in S1, because the strain responded at a higher rate for at least one reward type (food). Moreover, previous studies show that S1 mice exhibit good learning across a range of operant- and maze-based behavioral assays (Clapcote & Roder, 2004; Holmes et al, 2002; Merritt & Rhodes, 2015). Thus, the lesser responding for ethanol-containing solutions in S1 mice likely reflects the aversion to ethanol, whether straight or sweetened, that has been reported in this strain previously (Rhodes et al, 2007; Yoneyama et al, 2008).…”
Section: Discussionmentioning
confidence: 94%
“…This difference was not due to gross learning or motoric effects in S1, because the strain responded at a higher rate for at least one reward type (food). Moreover, previous studies show that S1 mice exhibit good learning across a range of operant- and maze-based behavioral assays (Clapcote & Roder, 2004; Holmes et al, 2002; Merritt & Rhodes, 2015). Thus, the lesser responding for ethanol-containing solutions in S1 mice likely reflects the aversion to ethanol, whether straight or sweetened, that has been reported in this strain previously (Rhodes et al, 2007; Yoneyama et al, 2008).…”
Section: Discussionmentioning
confidence: 94%
“…Several studies have demonstrated that increasing production of adult born neurons in the hippocampus; that is increasing adult neurogenesis levels improves performance in context discrimination while decreasing neurogenesis has the opposite effect (Clemenson et al, 2015; D. J. Creer, C. Romberg, L. M. Saksida, H. van Praag, & T. J. Bussey, 2010; Danielson et al, 2016; Frankland et al, 1998; Merritt & Rhodes, 2015; Sahay et al, 2011). Young neurons are more sensitive to perforant pathway input necessary for driving the encoding of new contexts (Frankland et al, 2013; Lacar et al, 2014; Wojtowicz, 2012).…”
Section: 0 Discussionmentioning
confidence: 99%
“…Alternatively, the mouse strain used in the current study (generated on a BL6129 background) may have been a confounding factor by potentially limiting our ability to detect any downregulation of new neurons. In several independent studies examining the role of genetic influence on the baseline level of hippocampal neurogenesis, the B6129SF1 and 129Sv were among the strains showing the lowest levels of newborn neurons (Clark et al, ; Kempermann, Kuhn, & Gage, ; Merritt & Rhodes, ).…”
Section: Introductionmentioning
confidence: 99%